Pemeriksaan Kadar Asam Urat Dan Konseling Di Kelurahan Bercak Wonosamudro Boyolali Jawa Tengah - Joko Tri Atmojo; Ndaru Syukma Putra; Ahmad Syauqi Mubarok; Asruria Sani Fajriah; Aris Widiyanto (Poltekkes Kemenkes Surakarta, 2021)
Background: Uric acid is a disease that arises from excessive blood uric acid levels, which causes excessive blood uric acid levels, which is the production of more uric acid in the body from its disposal. There are several causes of gout, including changes in diet, consumption of drugs, and alcohol consumption. The purpose of implementing this community service activity is to provide education to the community in Bercak Village and to check uric acid levels. Methods: Based on the team's observations on several residents in Bercak Village, it was found that most residents did not have sufficient knowledge about gout and did not carry out routine health checks. In order to increase awareness and understanding of residents about health care efforts, especially preventing gout, the team coordinated with the urban village to carry out community service activities in Bercak Village, Wonosamudro, Boyolali. Results: The target in implementing this program is all residents in the Bercak Village, Wonosamudro, Boyolali. Community service activities were carried out on March 13, 2021, attended by the village head and also village officials and babinsa. Conclusion: After carrying out the activity, it is hoped that the community can follow up on the results of the examination and improve the behavior of efforts to prevent gout.